Влияние гуматов на ризогенез некоторых видов рода Sedum L. (Crassulaceae DC.) - Попова, Л.В.; Бутюгин, А.В. (Промышленная ботаника, 2006)
The article represents the results of studying of humic stimulators impact on root-forming ability of 2 species of the genus Sedum L. (Crassulaceae DC.). The humic stimulators are on the basis of brown coal ammonium humates with different variants of microelements additions of copper, zinc, boron, molybdenum, cobalt, germanium. It is established, that the studied humates may be recommended in order to receive a great number of planting material when taking root of S. middendorffianum cuttings; but using of the humates is inexpedient when taking root of S. caucasicum cuttings.